Uncovering the spatial heterogeneity of Ediacaran carbon cycling. Issue 2 (20th December 2016) - Li, C.; Hardisty, D. S.; Luo, G.; Huang, J.; Algeo, T. J.; Cheng, M.; Shi, W.; An, Z.; Tong, J.; Xie, S.; Jiao, N.; Lyons, T. W.
Abstract: Records of the Ediacaran carbon cycle (635–541 million years ago) include the Shuram excursion (SE), the largest negative carbonate carbon isotope excursion in Earth history (down to −12‰). The nature of this excursion remains enigmatic given the difficulties of interpreting a perceived extreme global decrease in the δ 13 C of seawater dissolved inorganic carbon. Here, we present carbonate and organic carbon isotope (δ 13 Ccarb and δ 13 Corg ) records from the Ediacaran Doushantuo Formation along a proximal‐to‐distal transect across the Yangtze Platform of South China as a test of the spatial variation of the SE. Contrary to expectations, our results show that the magnitude and morphology of this excursion and its relationship with coexisting δ 13 Corg are highly heterogeneous across the platform. Integrated geochemical, mineralogical, petrographic, and stratigraphic evidence indicates that the SE is a primary marine signature. Data compilations demonstrate that the SE was also accompanied globally by parallel negative shifts of δ 34 S of carbonate‐associated sulfate (CAS) and increased 87 Sr/ 86 Sr ratio and coastal CAS concentration, suggesting elevated continental weathering and coastal marine sulfate concentration during the SE. In light of these observations, we propose a heterogeneous oxidation model to explain the high spatial heterogeneity of the SE and coexisting δ 13 Corg records of the Doushantuo, with likely relevance to the SE in other regions. In this model, we infer continued marine redox stratification through the SE but with increased availability of oxidants (e.g., O2 and sulfate) limited to marginal near‐surface marine environments. Oxidation of limited spatiotemporal extent provides a mechanism to drive heterogeneous oxidation of subsurface reduced carbon mostly in shelf areas. Regardless of the mechanism driving the SE, future models must consider the evidence for spatial heterogeneity in δ 13 C presented in this study.